A Case Report and Literature Review of a Novel Mutation in the MAGED2 Gene of a Patient With Severe Transient Polyhydramnios - Wu, Xiaoxia; Huang, Le; Luo, Caiqun; Liu, Yang; Niu, Jianmin (Frontiers in Pediatrics, 2021)
Background: Polyhydramnios occurs frequently during pregnancy. Mutations in the MAGED2 gene can cause X-linked acute early-onset polyhydramnios with a severe but transient form of antenatal Bartter’s syndrome. Case presentation: Here, we report a new novel frameshift mutation c.733_734delCT (p. Leu245GlufsTer4) in the MAGED2 gene (NM_177433.1) that caused prenatal polyhydramnios, but did not cause polyuria after birth. Follow-up was conducted for 2 months, and the baby’s growth and development were normal, without polyuria and renal impairment. In addition, we identified all individuals with MAGED2 mutations reported in the literature before March 2021. Conclusion: We report a new case with a novel variant of the MAGED2 gene that caused severe hydramnios but with a good result and summary clinical characteristics in a newborn with antenatal Bartter’s syndrome caused by an MAGED2 mutation. Good prenatal diagnosis and genetic consultation can improve pregnancy monitoring and newborn management.